Macromol. Chem. Phys. 5/2013. Issue 5 (28th February 2013) - Julich‐Gruner, Konstanze K.; Löwenberg, Candy; Neffe, Axel T.; Behl, Marc; Lendlein, Andreas
<x xml:space="preserve">Abstract</x> Front Cover: Shape‐memory polymers can be created in a modular approach, consisting of three components: chain segments, permanent netpoints and temporary netpoints. Varying these components enables the integration of several functions, as well as the implementation of multistimuli‐sensitivity in shape‐memory polymers. Further details can be found in the article by Konstanze K. Julich‐Gruner, Candy Löwenberg, Axel T. Neffe, Marc Behl, and Andreas Lendlein* on page 527. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>